PENGEMBANGAN APLIKASI PENCARIAN REKOMENDASI ASISTEN LABORATORIUM KOMPUTER DENGAN METODE SIMPLE ADDITIVE WEIGHTING: STUDI KASUS : INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE - Humdiana; Michael (Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Technological developments are growing day by day. The growing technology proves that human beings are able to create new things that can help in completing their work. With the development of technology, we can also be facilitated in taking decisions, such as in choosing human resources. This research is motivated by the absence of an objective calculation in the selection of computer lab assistants, the difficulty of determining the weight in the criteria of the selection of computer lab assistants, and the selection process that is still running manually. This research is done by using NoSql Firebase as a database, using Java and XML language, and Android Studio as tools to develop this application. Researchers apply the method of Simple Additive Weighting in searching for recommendations of computer lab assistants. Information gathering was done by field study, ie direct observation and interviews with the head of computer lab assistant, and literature study such as reading books, journals, and websites as supporting reference for this research. This application was created to implement the selection of computer lab assistants to be more objective and can assist in the search of computer lab assistant recommendations. Through the research process that has been done and the application development process that has been going on, the researcher concludes that the application that the researcher produces can provide the recommendation of computer lab assistants objectively and precisely, and get the weight on each criterion well. Keywords: Simple Additive Weighting Method, Computer Laboratory Assistant, Android